MicroRNA-mediated regulation of the immune response in Calu-3 cells infected with a SARS-CoV-2 E gene variant - Sun, Chenfan; Xu, Fang; Pu, Zhongji; Zhu, Han-Ping; Li, Yu-dong; Lu, Hang-Jing; Wu, Bei-Bei; Sun, Yi-Sheng; Yao, Ping-Ping; Jiang, Jian-Ming (Frontiers in Microbiology, 2025)
IntroductionSARS-CoV-2, the pathogen of COVID-19, disrupts the alveolar epithelial barrier and triggers exacerbation of airway inflammation. The envelope (E) protein plays a key role in promoting epithelial damage and sustaining inflammation. We previously identified a SARS-CoV-2 variant (F8) containing a 12-bp deletion in the E gene. Compared to the 8X strain, which possesses the wild-type E gene, F8 could induce a higher expression of inflammatory factors in Calu-3 cells.MethodsThis study analyzed the miRNA expression profiles in Calu-3 cells infected with either the F8 variant or the 8X strain. Quantitative Reverse Transcription Polymerase Chain Reaction (RT-qPCR) was employed to validate the differential expression of candidate miRNAs. Subsequent functional verification assays like ELISA were performed to elucidate the regulatory roles of these miRNAs in host signaling pathways, such as inflammatory responses.ResultsWe discovered that F8 infection significantly upregulated miR-361-3p and downregulated let-7b-5p. Furthermore, miR-361-3p regulated the PI3K-Akt pathway by directly targeting and inhibiting TSPAN1, ultimately promoting PTEN expression. The downregulation of let-7b-5p might release the suppression on inflammatory cytokines (IL-6, IL-8, PTX3), and partially disorder ZO-1 expression in maintaining the barrier function.DiscussionThis study is the first to demonstrate that the SARS-CoV-2 E protein mutant F8 remodeled the host miRNAs network to coordinate the immune responses and barrier function. All findings provided valuable insights into the pathogenesis of SARS-CoV-2 variants.